Peran Infrastruktur Kesehatan pada Ketimpangan Pendapatan di Indonesia Tahun 2018-2023 - Citra Ayu Aprianing; Suharno Suharno (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Income inequality is a problem that exists in many countries including Indonesia with a moderate level of income inequality that has been going on for a long time since 2010, so the purpose of this study is to analyze what factors and how these factors affect income inequality in Indonesia. The independent variables used are the Open Unemployment Rate (TPT), Foreign Investment (IA) and the Number of Health Centers (JP). The analysis tool used is the Generalized Method of Moment on panel data from 2015 to 2023. The results of the study are as follows: (1) TPT and IA have a significant positive effect on income inequality; (2) JP has a negative but insignificant effect on income inequality; (3) TPT and IA have a significant positive effect on income inequality in the short term of 3.187% and 0.004% and 91.953% and 13.265% in the long term; (4) JP has a negative but insignificant effect on income inequality of 0.002% in the short term and 6.4% in the long term; (5) TPT, IA and JP variables together have an effect on income inequality.